Understanding User Satisfaction in Stock Investment Apps through Information Quality and Perceived Ease of Use - Ammar Shiddiq Yulianto; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This research investigates how perceived ease of use and information quality shape user satisfaction with stock investment applications in Indonesia by surveying 120 active users with a 16-item, five-point Likert questionnaire and analyzing the data using multiple linear regression. The results show that information quality has a stronger positive impact on user satisfaction than perceived ease of use, and together both variables account for 77.1% of the variation in satisfaction. These outcomes indicate that users of stock investment platforms value accurate and timely data more highly than simple interfaces. The study therefore concludes that information quality and perceived ease of use are both key drivers of satisfaction, with information quality being slightly more dominant. The implications suggest that fintech developers should strategically balance investment in robust data infrastructure and user interface design to enhance user satisfaction and sustain their platforms.